2022
DOI: 10.1039/d2en00623e
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial-modulated cellular sodium extrusion and vacuolar sequestration for salt tolerance

Abstract: Nanomaterials can induce plant tolerance to abiotic environmental stresses, whereas the sensing mechanism and the resulting response at cellular level need further exploration. Bright Yellow 2 tobacco (Nicotiana tabacum L.)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Bacterial cell membrane is known as a barrier against HGT, inhibiting the transfer of eDNA into cells [ 45 , 46 ] ( Figure 4 a,b). Our previous work showed that CeO 2 NPs at low concentrations exhibited an efficient ROS scavenging capacity [ 47 ]. In System 1, although CeO 2 NPs at 10–50 mg L −1 increased the ROS level by 1.1-fold, ( Figure 4 c), the cell membrane permeability remained unchanged for all concentrations, and was confirmed by the expression pattern of genes related to membrane permeability and the SOS response ( Figure 4 d,e).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial cell membrane is known as a barrier against HGT, inhibiting the transfer of eDNA into cells [ 45 , 46 ] ( Figure 4 a,b). Our previous work showed that CeO 2 NPs at low concentrations exhibited an efficient ROS scavenging capacity [ 47 ]. In System 1, although CeO 2 NPs at 10–50 mg L −1 increased the ROS level by 1.1-fold, ( Figure 4 c), the cell membrane permeability remained unchanged for all concentrations, and was confirmed by the expression pattern of genes related to membrane permeability and the SOS response ( Figure 4 d,e).…”
Section: Resultsmentioning
confidence: 99%
“…43 Additionally, previous studies have shown that NPs (e.g., carbon quantum dots, CeO 2 NPs) could promote Ca 2+ influx in plants owing to the small size effect of particles. 34,44 We thus speculated that nanoscale MSNs could also promote Ca 2+ influx. Moreover, phytohormones are critical regulators mediating plant resistance against herbivore infestation.…”
Section: Cs-msns Triggering Leaf Calcium and Phytohormone Signalingmentioning
confidence: 99%